Of Pride and Prejudice—A Cross-National Exploration of Atheists’ National Pride - Bechert, Insa (Religions, 2021)
This paper explores how atheism relates to national pride. Previous research reports the strong positive relationship between religiosity and national pride. Inversely, it can be assumed that atheists feel less national pride. Whether this assumption holds true and whether the perceived relevance of religiosity for values perceived as fundamental for national pride is a national-specific or a global phenomenon will be investigated here by examining attitudes towards atheists and assessing cross-nationally how proud atheists truly are of their countries. The data reveals cross-country differences in both respects. In highly religious countries, prejudice against atheists is pronounced, while atheists’ feelings of national pride indeed tend to be weaker. But what exactly predicts atheists’ feelings of national pride? For a Multilevel Analysis of this question, this article uses the ONBound database offering cumulated and harmonized data from international survey programs as well as linked country-level data on national identities and religion. Results identify countries’ ideological background as one of the crucial country-level predictors for national pride among atheists. In highly religious countries, people who deny religion also seem to possess ambivalent feelings towards their country. In turn, if the state ideology opposes religion, atheists tend to support the combination of anti-religiousness and patriotism.